Two-dimensional para-, ortho-, and bi-magnetoexcitons interacting with quantum point vortices - Moscalenco, Sveatoslav (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2018)
The theory of two-dimensional (2D) magnetoexcitons was enlarged taking into account the electron–hole (e–h) exchange Coulomb interaction, which appears when the conduction and valence electrons belong partially to both bands. This Coulomb exchange interaction leads to the linear dispersion law of para-magnetoexcitons. Spectral properties and the new luminescence band, which arise owing to the existence of the metastable bound state, are discussed. The thermodynamic properties and the Bose–Einstein condensation conditions for para- and ortho-magnetoexcitons are described. Taking into account the vector potential of the Chern–Simons gauge field the anisotropy of the 2D magnetoexciton magnetic mass was revealed.